2012
DOI: 10.5603/fhc.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

BOX-PCR is an adequate tool for typing of clinical <i>Pseudomonas aeruginosa</i> isolates

Abstract: Abstract:In this study, the BOX-PCR fingerprinting technique was evaluated for the discrimination of clinical Pseudomonas aeruginosa isolates. All isolates were typeable and nearly half showed unique banding patterns. According to our results, BOX-PCR fingerprinting is applicable for typing of Pseudomonas aeruginosa isolates and can be considered a useful complementary tool for epidemiological studies of members of this genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…The use of 272 and 208 primers was successful in discrimination of different Pseudomonas isolates described before ( 28 ). Although Nagaveni et al ( 51 ) showed that ERIC PCR provided an exceptionally qualitative discrimination for pseudomonads, the results of our and similar studies ( 52 , 53 ), showed the advantage of BOX PCR, as it confirmed the results obtained with 272 RADP PCR.…”
Section: Resultssupporting
confidence: 83%
“…The use of 272 and 208 primers was successful in discrimination of different Pseudomonas isolates described before ( 28 ). Although Nagaveni et al ( 51 ) showed that ERIC PCR provided an exceptionally qualitative discrimination for pseudomonads, the results of our and similar studies ( 52 , 53 ), showed the advantage of BOX PCR, as it confirmed the results obtained with 272 RADP PCR.…”
Section: Resultssupporting
confidence: 83%
“…BOX-PCR produced a larger number (6) of duplicate profiles (Figure 4 ), i.e., a larger number of identical strains, than the number (3) obtained from ERIC-PCR (Figure 3 ). Previous studies gave similar degrees of heterogeneity by application of rep-PCR analysis in groups of isolated Pseudomonas strains (Selvakumar et al, 2009 ; Vyas et al, 2009 ; Wolska et al, 2011 ).…”
Section: Resultsmentioning
confidence: 72%
“…ERIC and BOX fingerprinting were used for typing strains of different Pseudomonas species (Wolska et al, ). These methods generates characteristic genome profiles that help to differentiate between closely related bacterial strains (Abdellatif et al, ; Rombouts et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The rep‐PCR fingerprinting analysis was carried out using the genomic DNA from each strain and primer sets BOXA1R (5′‐CTACGGCAAGGCGACGCTGACG‐3′) (Martin et al, ) and E1 (5'‐ATGTAAGCTCCTGGGGATTCAC‐3') and E2 (5'‐AAGTAAGTGACTGGGGTGACGG‐3') (Versalovic, Schneider, de Bruijn, & Lupski, ), corresponding to BOX and ERIC elements, respectively. The PCR protocol was adapted from Wolska, Kot, Jakubczak, and Rymuza (). Amplification was carried out in a total volume reaction of 50 µl containing 1× PCR Taq Reaction Buffer (Thermo Fisher Scientific), 2.5 mM dNTP, 2.5 mM MgCl 2 , 2 µM of each primer, 150 ng genomic DNA template and 1.25 unit Taq DNA Polymerase (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%